N‐cadherin Regulation of Bone Growth and Homeostasis Is Osteolineage Stage–Specific. (29th March 2017) - Fontana, Francesca; Hickman‐Brecks, Cynthia L; Salazar, Valerie S; Revollo, Leila; Abou‐Ezzi, Grazia; Grimston, Susan K; Jeong, Sung Yeop; Watkins, Marcus; Fortunato, Manuela; Alippe, Yael; Link, Daniel C; Mbalaviele, Gabriel; et al.
ABSTRACT: N‐cadherin inhibits osteogenic cell differentiation and canonical Wnt/β‐catenin signaling in vitro. However, in vivo both conditional Cdh2 ablation and overexpression in osteoblasts lead to low bone mass. We tested the hypothesis that N‐cadherin has different effects on osteolineage cells depending upon their differentiation stage. Embryonic conditional osteolineage Cdh2 deletion in mice results in defective growth, low bone mass, and reduced osteoprogenitor number. These abnormalities are prevented by delaying Cdh2 ablation until 1 month of age, thus targeting only committed and mature osteoblasts, suggesting they are the consequence of N‐cadherin deficiency in osteoprogenitors. Indeed, diaphyseal trabecularization actually increases when Cdh2 is ablated postnatally. The sclerostin‐insensitive Lrp5 A214V mutant, associated with high bone mass, does not rescue the growth defect, but it overrides the low bone mass of embryonically Cdh2 ‐deleted mice, suggesting N‐cadherin interacts with Wnt signaling to control bone mass. Finally, bone accrual and β‐catenin accumulation after administration of an anti‐Dkk1 antibody are enhanced in N‐cadherin–deficient mice. Thus, although lack of N‐cadherin in embryonic and perinatal age is detrimental to bone growth and bone accrual, in adult mice loss of N‐cadherin in osteolineage cells favors bone formation. Hence, N‐cadherin inhibition may widen the therapeutic window of osteoanabolic agents. © 2017 American Society for Bone and Mineral Research.